Liquid-like lithium ion conductivity in Li4-3xAlxGeO4 solid electrolyte - Chnoong, Kheng Lee; West, Anthony R. (Royal Society of Chemistry, 1991)
The solid solutions Li4-3xAlxGeO4 have a high conductivity which is independent of temperature above 700°C, e.g. 0.23 Ω-1 cm-1 for x = 0.10. A small fraction of the lithium ions appear to be in zero activation energy, liquid-like motion. Zero activation energy for ionic conduction is rare in crystalline materials and this is the first example observed for Li+ ions.